Community Composition of Epibiont Hydroids of the Naturalized Alien Macroalga Acanthophora spicifera in Pichilingue, Mexico - Jessica Licona Angeles; Francisco Rubén Castañeda Rivero; María A. Mendoza-Becerril (Biology)
This study provides a detailed analysis of the community of hydrozoan epibionts of Acanthophora spicifera in La Paz Bay, Baja California Sur. The investigation was carried out in two season periods, corresponding to the warm and cold seasons on the pier of the Autonomous University of Baja California Sur (UABCS) Pichilingue research station. The percentage of epibiont coverage was calculated and analyzed. The average length of the thalli was 7.8 ± 4.6 cm. Eleven taxa of hydrozoans were recorded; the hydrozoan Obelia cf. dichotoma had the highest coverage percentage, and in summer, there was a higher taxa richness. It is recommended to monitor this macroalga and its epibionts for its wide distribution in the bay, although in UABCS, Pichilingue Pier has not seen epibionts that threaten biological diversity.